Study of $D_{sJ}$ decays to $D^+\KS$ and $D^0K^+$ final states in $pp$ collisions - collaboration, L; Aaij, R; Beteta, C; Adametz, A; Adeva, B; Adinolfi, M; Adrover, C; Affolder, A; Ajaltouni, Z; Albrecht, J; Alessio, F; Alexander, M; et al. (Springer-Verlag, 2012)
A study of $D^+\KS$ and $D^0K^+$ final states is performed in a sample of 1.0/fb of $pp$ collision data collected at a centre-of-mass energy of $\sqrt{s}=7$ TeV with the \lhcb detector. We confirm the existence of the $D_{s1}^*(2700)^+$ and $D_{sJ}^*(2860)^+$ excited states and measure their masses and widths to be {eqnarray} m(D_{s1}^*(2700)^+) and=and 2709.2 ± 1.9({stat})±\,\,\,4.5({syst}) MeV/c^2,\cr Γ(D_{s1}^*(2700)^+) and=and \,\,\,115.8 ± 7.3({stat}) ±12.1({syst}) MeV/c^2,\cr m(D_{sJ}^*(2860)^+) and=and 2866.1 ± 1.0({stat}) ±\,\,\,6.3({syst}) MeV/c^2,\cr Γ(D_{sJ}^*(2860)^+) and=and \,\,\,\,\,\,69.9 ± 3.2({stat}) ±\,\,\,6.6({syst}) MeV/c^2.\cr {eqnarray}